The Challenge of Building Proper Urban Indicator System: A Proposal for Croatian Cities - Dubravka Jurlina Alibegovic; Zeljka Kordej De Villa (European Regional Science Association (ERSA), 2006)
In this paper, urban indicator system is investigated in the context of urban policy processes. Indicators are seen as a tool to enhance urban management and special attention is given to their role in providing assistance in monitoring municipal development and performance. The paper will present desirable features of useful indicators from the city perspective, as well as framework to include these indicators in urban policy and management successfully. Formulation of proper indicator system requires a good understanding of the utilization, diffusion and dissemination of information in policy processes, so the paper will consider basic constraints related to these preconditions such as existing knowledge gaps within the indicator developer community vs. their theoretical limitations, communication concerns, human and technical capacities, policy issues etc. This paper will also elaborate modest Croatian experience in developing urban indicator system and lessons learned will be used as guidelines in making illustrative proposal for Croatian cities. In addition, this paper will try to define particular environmental, economic and governance variables/indices that should be adopted as urban indicators, taking in account Croatian specificities. We conclude this paper by addressing future challenges related to integration of urban indicator system within urban policy in Croatia.
Keywords: 330